2005
DOI: 10.1021/ja053981u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Two Types of Nanoparticles in Polyelectrolyte Capsule Nanoreactors and Their Dual Functionality

Abstract: Polyelectrolyte multilayer capsule reactors (PEMCRs) for the synthesis of two types of nanoparticles were prepared. The tunable PEMCRs containing two different functional groups that can be used to synthesize two types of nanoparticles simultaneously and to control the composition of two types of nanoparticles within the shell of PEMCs. These PEMCRs enabled the composition as well as the amount of the loaded two types of nanoparticles within the shell of PEMCs to be controlled by the copolymer ratio and the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Integration of nanoparticles with polymer capsules is desirable for multifunctional applications (release of cargo, enhance mechanical properties, etc) [14], [15], and can be achieved by incorporating nanoparticles within the two available compartments in PEM capsules, namely- shell and the cavity. To this end of loading nanoparticles in the shell of polymer capsules, few reports are available on the development of multifunctional PEM capsules which possess optical/magnetic nanoparticles sandwiched between the PEM layers along with the prospect of filling the cavity with desirable cargo [16][19]. Koo et al have reported loading of gold nanorods on the surface of polymer capsules [20].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of nanoparticles with polymer capsules is desirable for multifunctional applications (release of cargo, enhance mechanical properties, etc) [14], [15], and can be achieved by incorporating nanoparticles within the two available compartments in PEM capsules, namely- shell and the cavity. To this end of loading nanoparticles in the shell of polymer capsules, few reports are available on the development of multifunctional PEM capsules which possess optical/magnetic nanoparticles sandwiched between the PEM layers along with the prospect of filling the cavity with desirable cargo [16][19]. Koo et al have reported loading of gold nanorods on the surface of polymer capsules [20].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are only few examples of antibacterial delivery system based on polyelectrolyte microcapsules. These examples employed the biocide‐leaching strategy either by inserting an antibacterial drug, ciproflaxine, into the core or shell of the capsule33, 34 or by inserting nanoparticles into the shell of the capsules 35…”
Section: Introductionmentioning
confidence: 99%
“…Many of the systems currently in progress, particularly those for molecule entrapment and delivery, draw their inspiration by an elegant, environmentally benign and simple process based on the layer-by-layer (LbL) self-assembly technology [3,4]. Different multilayered carriers composed of polyelectrolytes or other macromolecules have been developed on nano-scale for successful incorporation of functional substances such as dyes [5], proteins [6], enzymes [7,8], cells [9] and inorganic crystals [10,11]. And relevant studies focused essentially on physical, chemical and biological properties with respect to these novel structures [12][13][14].…”
Section: Introductionmentioning
confidence: 99%